MAPPING DISTRIBUTION OF INFORMAL FOOD STALLS AT SUDIRMAN STREET DURI CITY MANDAU DISTRICT - NURMALA SARI, DWI; Juita, S.Pd. M.Si, Erna; Zuriyani, M.Si, Elvi (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Â This study aims to determine the distribution of informal food stalls at Sudirman Street Duri City Mandau District, seen from: the distribution, pull factors, impact of street vendors and government efforts to overcome the problem of street vendors.This research is descriptive quantitative. Data were analyzed using the nearest neighbor and map analysis and interviews, conducted general research Sudirman Street Duri City Mandau District.The results of the study found that : 1) Distribution of informal food stalls at street of Sudirman Street Duri City Mandau District is an area that has a clustered pattern (clumped), (2) factors affecting informal food stalls at Â Sudirman Street Duri City Mandau District is informal food stalls (PKL) feel there is a place that is now comfortably occupied and strategic, in the main street and a lot of consumers, (3) the impact of the presence of informal food stalls at Sudirman Street Duri City Mandau District t is generally hamper traffic as merchants wear shoulder of the road as a place of trade and (4) the governments efforts against informal food stalls is to provide guidance through counseling and enforcement both oral and written.